2020
DOI: 10.1002/em.22395
|View full text |Cite
|
Sign up to set email alerts
|

A stapled POL κ peptide targets REV1 to inhibit mutagenic translesion synthesis

Abstract: Stapled α-helical RIR (Rev1-interacting region) peptides of DNA POL κ bind more effectively to the RIR-interface of the C-terminal recruitment domain of the translesion synthesis DNA polymerase Rev1 than unstapled peptide. The tightest-binding stapled peptide translocates into cells and enhances the cytotoxicity of DNA damaging agents while reducing mutagenesis. Drugs with these characteristics could potentially serve as adjuvants to improve chemotherapy and reduce acquired resistance by inhibiting Rev1-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…This could also serve as an opportunity to recruit Pol ζ, which would efficiently extend from the bypassed DNA lesion (13). Importantly, inhibiting the interaction of Rev1 with other TLS polymerases was recently shown as a promising therapeutic target in cancer (40)(41)(42). Therefore, future work is necessary to fully understand the interplay between the nonprocessive nature of Rev1 and the scaffolding function during the polymerase switch.…”
Section: Organization Of Substrates and Products Within The Rev1 Active Sitementioning
confidence: 99%
“…This could also serve as an opportunity to recruit Pol ζ, which would efficiently extend from the bypassed DNA lesion (13). Importantly, inhibiting the interaction of Rev1 with other TLS polymerases was recently shown as a promising therapeutic target in cancer (40)(41)(42). Therefore, future work is necessary to fully understand the interplay between the nonprocessive nature of Rev1 and the scaffolding function during the polymerase switch.…”
Section: Organization Of Substrates and Products Within The Rev1 Active Sitementioning
confidence: 99%
“…These landmark observations provide a semblance as to why the cancer mutational spectrum continues to evolve and an understanding as to why there remains a continuity to clinical challenges in treating patients. Furthermore, the discovery of REV1 inhibitors provided a reliable platform for potential clinical adjuvant therapy [2][3][4][5] . However, indications that REV1 inhibition can also switch the underlying biology of cancer cells, whereby it can suppress apoptosis in cisplatin-treated cells, and trigger senescence 8 , suggested that REV1 may have a larger new role in cancer pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This study tested whether REV1 inhibition via CTD-specific small molecule inhibitors sensitizes cancer cells to radiation treatment. In contrast to their chemosensitization effects [2][3][4][5]8 , REV1 inhibition failed to sensitize cancer cells to ionizing radiation. We confirmed the lack of radiosensitization by using five different REV1 inhibitors, varying doses of REV1 inhibitors, testing physiologically relevant increasing ionizing radiation doses, and examining radioresistant cell lines.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Intrinsic and acquired resistance to DNA-damaging cancer therapy is a persistent clinical challenge that ultimately limits successful clinical outcomes in patients [ 1 ]. Recent evidence suggests that a possible strategy to sensitize tumors and reduce chemotherapy resistance is to inhibit the mutagenic translesion synthesis (TLS) pathway by targeting REV1 TLS polymerase [ 2 , 3 , 4 , 5 ]. Translesion synthesis is a DNA damage bypass process involving a set of specialized DNA polymerases that collectively tolerate DNA damage and cause mutations [ 1 ].…”
Section: Introductionmentioning
confidence: 99%